Arabidopsis AtPLC2 Is a Primary Phosphoinositide-Specific Phospholipase C in Phosphoinositide Metabolism and the Endoplasmic Reticulum Stress Response - Kanehara K. (Public Library of Science, 2018)
10.1371/journal.pgen.1005511